Antibodies to the RNA binding protein heterogeneous nuclear ribonucleoprotein A1 contribute to neuronal cell loss in an animal model of multiple sclerosis. Issue 10 (11th January 2020) - Libner, Cole D.; Salapa, Hannah E.; Hutchinson, Catherine; Lee, Sangmin; Levin, Michael C.
Abstract: Neurodegeneration, including loss of neurons and axons, is a feature of progressive forms of multiple sclerosis (MS). The mechanisms underlying neurodegeneration are mostly unknown. Research implicates autoimmunity to nonmyelin self‐antigens as important contributors to disease pathogenesis. Data from our lab implicate autoimmunity to the RNA binding protein (RBP) heterogeneous nuclear ribonucleoprotein A1 (hnRNP A1) as a possible mechanism of neurodegeneration in MS. MS patients make antibodies to hnRNP A1, which have been shown to lead to neuronal dysfunction in vitro. Using an animal model of MS, experimental autoimmune encephalomyelitis (EAE), we show here that injection of anti‐hnRNP A1 antibodies, in contrast to control antibodies, resulted in worsened disease and increased neurodegeneration. We found a reduction of NeuN + neuronal cell bodies in areas of the ventral gray matter of the spinal cord where anti‐hnRNP A1 antibodies localized. Neurons displayed increased levels of hnRNP A1 nucleocytoplasmic mislocalization and stress granule formation, both markers of neuronal injury. Anti‐hnRNP A1 antibodies were found to surround neuronal cell bodies and interact with CD68 + immune cells via Fc receptors. Additionally, anti‐hnRNP A1 antibodies were found within neuronal cell bodies including those of the ventral spinocerebellar tract (VSCT), a tract previously shown to undergo neurodegeneration in anti‐hnRNP A1 antibody injected EAE mice. Finally, both immune cells and neurons showed increased levels of inducible nitric oxide synthase, another indicator of cell damage. These findings suggest that autoimmunity to RBPs, such as hnRNP A1, play a role in neurodegeneration in EAE with important implications for the pathogenesis of MS. Abstract : Multiple sclerosis (MS) patients, in contrast to healthy controls make autoantibodies to the RNA binding protein heterogenous nuclear ribonucleoprotein A1 (hnRNP A1). Using experimental autoimmune encephalomyelitis, an animal model of MS, injections of anti‐hnRNP A1 antibodies lead to increased neurodegeneration as shown by a loss of neuronal cell bodies in the ventral spinal cord (graph). We demonstrate that anti‐hnRNP A1 antibodies localized within and surrounding neuronal cell bodies of the ventral spinal cord. In these areas we demonstrate that neurons display increased hnRNP A1 mislocalization from the nucleus to the cytoplasm, increased stress granule formation while also expressing inducible nitric oxide synthase (iNOS). Additionally, anti‐hnRNP A1 antibodies were localized to CD16 + /CD68 + immune cells leading to an increase in iNOS in the surrounding tissue and subsequent neurodegeneration.